INTEGRATION OF ZAKAT AND TAX FOR ECONOMIC DEVELOPMENT - Muharani Nst, Junita; Nurhidayanti, Nurhidayanti; Hamdi, Abdul Ridho (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2020)
Zakat and tax is an instrument for collecting funds is expected to help the country's economy, but today these instruments have not been realized completely due to thinking their double burden. The type of research uses literature study using secondary data. Results of the discussion stated that the synergy of the tax and zakat in Indonesia's economic development is very important, because the tax and zakat have complementary usefulness. With synergy of tax and zakat, the economic development that is formed is a strong economy and can compete in the midst of the economic crisis that threatens.